CGIAR Research Program on Policies, Institutions, and Markets: Priorities for 2019–2021 - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2019)
The CGIAR Research Program on Policies, Institutions, and Markets (PIM) works with research and implementation partners in Africa, Asia, and Latin America to generate evidence, develop capacity, and support policies that help poor people, both men and women, improve their lives; produce nutritious and affordable foods; and protect the soil, water, and biodiversity in rural landscapes. Through work on technological innovation, rural transformation, value chains, social protection, natural resource governance, and gender, PIM research informs policies, strategies, programs, and investment decisions of governments, development organizations, NGOs, and private companies.